Health‐related quality of life and functionality in elderly men and women before and after a fall‐related wrist fracture. Issue 7 (25th March 2014) - González, N.; Aguirre, U.; Orive, M.; Zabala, J.; García‐Gutiérrez, S.; Las Hayas, C.; Navarro, G.; Quintana, J. M.
Summary Aims To evaluate health‐related quality of life (HRQoL) and functionality among older men and women who suffered a wrist fracture because of a fall and to identify postfracture consequences. Methods Observational, prospective cohort study of patients recruited in the emergency departments (ED) of six public hospitals of the Basque Health Service and one of the Catalan Health Service. Two groups of adults aged 65 or older were recruited: 960 with wrist fractures because of falls (fracture cohort) and 119 without fall‐related wrist fractures in the previous year (non‐fracture cohort). We collected sociodemographical and clinical data; general and specific HRQoL data measured by the 12‐Item Short Form Health Survey (SF‐12) and a short version of the Disabilities of the Arm, Shoulder, and Hand instrument (QuickDASH); and data about basic (BADL) and instrumental (IADL) activities of daily living, measured by the Barthel Index and the Lawton and Brody Index (LBI). Results Women with wrist fractures exhibited greater declines than men 6 months after the fall in all questionnaires except the LBI, and greater declines than those in the non‐fracture cohort independent of gender. Patients aged 80 years and older presented with worse baseline scores in all the outcome measures and lost more HRQoL and functionality after wrist fractures. Discussion Women and older individuals experienced the greatest reductions in HRQoL and functionality after a fall‐related wrist facture, suggesting that they might merit special attention in clinical care and public health policy. Conclusions Specific prevention strategies may be needed to avoid or reduce the consequences of fall‐related wrist fractures.